First Molecular Identification of Babesia ovis in Dogs: An Unexpected Host - Ulucesme, Mehmet Can; Karoglu, Aleyna; Barutcuoglu, Begum; Aktas, Munir; Ozubek, Sezayi (Univ Agriculture, Fac Veterinary Science, 2025)
Babesiosis, a tick-borne disease caused by various Babesia species, is primarily associated with livestock but has increasingly been reported in dogs worldwide. This research investigates the prevalence of Babesia species in shelter dogs located in Diyarbak & imath;r province, T & uuml;rkiye. Blood samples from 80 asymptomatic dogs were processed for DNA extraction, followed by nested PCR (nPCR) to amplify the 18S rRNA gene of Babesia (B.) and Theileria (T.) species. Sequencing and subsequent phylogenetic analysis of the positive cases identified B. ovis in 9 dogs (11.2%) and B. vogeli in 2 dogs (2.5%), marking the first molecular confirmation of B. ovis in dogs. Besides the two species of Babesia, Toxoplasma gondii was also detected incidentally from one sample. These findings provide novel evidence of B. ovis infection in dogs, highlighting potential cross-species transmission. The study underscores the critical need for continuous surveillance and molecular diagnostics to enhance our knowledge of tick-borne pathogen in dogs and their potential zoonotic risks. Further research is essential to clarify the role of dogs in the B. ovis transmission dynamics and to develop more targeted control strategies.
Keywords: Babesia ovis; Babesia vogeli; Canine babesiosis; Toxoplasma gondii; Unexpected host